Suitability of neurofeedback protocol for children with dyslexia / Zulkifli Mahmoodin ...[et al.] - Mahmoodin, Zulkifli; Mansor, Wahidah; Lee, Yoot Khuan; Ahmad Zainuddin, Ahmad Zuber (UiTM Press, 2018)
Dyslexia is viewed as a neurological defect that causes the subject’s electrophysiological brain signal to process information differently from that of a normal learner. Subjects exhibit learning disorder in the form of reading and writing difficulties even though they possess an average intelligence quotient (IQ) level among their age group. Current intervention programmes for dyslexia rely on intensive repetitive exercises in phonemic and phonetic awareness which could be counterproductive. This paper looks into the possible application of neurofeedback towards the treatment of neurobiological dysfunction related to dyslexia. Through training or conditioning exercises, neurofeedback practise the control of brain waves in reaching a state most appropriate for a given situation. By understanding the alternate pathway of learning in capable dyslexic learner and looking into its application in various other neurobiological dysfunction, the potential neurofeedback for the treatment of dyslexia are discussed.